The Influence of Brand Image, Brand Trust, and Brand Love on Brand Loyalty Hos of Shopaholic - Nurjanah, Eva; Ariani, Dorothea Wahyu (LifeSciFi, 2024)
This research aims to analyze the influence of brand image, brand trust, and brand love on brand loyalty. The subjects of this research were users of House of Shopaholic products in the Special Region of Yogyakarta. The sample in this study consisted of 150 respondents selected using purposive sampling. Data collection was carried out using a questionnaire. The analysis used in this research is multiple linear regression, and the data analysis technique employed IBM SPSS 22 software. Based on the research results, it was found that: brand image has a positive and significant effect on brand loyalty, brand trust has no effect on brand loyalty, and brand love has a positive and significant effect on brand loyalty. These findings indicate that to increase brand loyalty, companies need to pay attention to and enhance brand image and cultivate brand love among consumers.